اختيارات الإمام ابن باديس في التفسير من خلال السور النمل يس الذاريات الفلق جمعًا ودراسة - كنزة هڨي (university of eloued جامعة الوادي, 2025)
موضوع الدراسة موسوم ب: اختيارات العلامة بن باديس في التفسير من خلال السورة من آيات النمل، يس، الذاريات، الفلق جمعا ودراسة. والإشكال الرئيسي الذي حاولت الإجابة عنه كالآتي: ماهي الاختيارات الشيخ ابن باديس في تفسيره مجالس التذكير في السور النمل, يس, الذاريات, الفلق وقد جاءت الدراسة مقسمة الى ثلاثة مباحث: خصص المبحث الأول: للتعريف بحدود البحث, والثاني والثالث: للدراسة التطبيقية, وجاء فيهما بيان اختيارات الشيخ ابن باديس في تفسيره لسورتي (النمل, يس, الذاريات, الفلق وخلاصة البحث وصلنا إلى جملة من النتائج أهمها وجود وحضور الرأي الشخصي للعلامة ابن باديس في تفسيره التي ابدعت في استنباط الهِدايات القرآنية وإسقاطها على أرض الواقع. ومن أهم التوصيات: التي تزيد خدمة الموضوع: إعداد رسائل اكاديمية تعنى بدراسة الاختيارات في تفسير الشيح ابن باديس. The topic of the study is titled: The Choices of Scholar Ibn Badis in Interpretation Through the Surahs of Verses (An-Naml, Yasin, Adh-Dhariyat, Al-Falaq) - Compilation and Study. The main issue I attempted to answer is: What are the choices of Sheikh Ibn Badis in his interpretation Majalis At-Tadhkir in the surahs (An-Naml, Yasin, Adh-Dhariyat, Al-Falaq)? The study is divided into three sections: The first section is dedicated to defining the boundaries of the research, and the second and third sections are for practical study, detailing the choices of Sheikh Ibn Badis in his interpretation of the surahs (An-Naml, Yasin, Adh-Dhariyat, Al-Falaq). The conclusion of the research reached several results, the most important of which is the presence and involvement of Scholar Ibn Badis's personal opinion in his interpretation, which innovatively extracted Quranic guidance and applied it to real life. Among the most important recommendations to enhance the subject are the preparation of academic theses focusing on studying the choices in the interpretation of Sheikh Ibn Badis.
مدكرة ماستر
Keywords: اختيارات النمل سورة الذاريات Choices An-Naml Surah Adh-Dhariyat